Antenatal diagnostic aspects of placenta percreta and its influence on the perinatal outcome: a clinical case and literature review - Volochovič, Jelena; Ramašauskaitė, Diana; Šimkevičiūtė, Ramunė (Acta medica Lituanica, 2017)
Background. Placenta percreta is a very rare, but extremely life-threatening obstetrical pathology for the mother and the child, especially in the cases when it is not diagnosed before the birth and when it results in massive bleeding and a dramatic deterioration of condition. It is extremely important to diagnose this pathology as early as possible and plan further optimal care of patients in order to minimize life-threatening complications. Case report. The paper presents an illustrated clinical case of placenta percreta determined before the birth. Features of visual diagnostics are discussed. A 32-year-old pregnant woman with a history of two caesarean deliveries arrived at the tertiary level hospital at 22 weeks of gestation due to abdomen pain. Placenta previa was diagnosed and ultrasound, magnetic resonance imaging suggesting placenta percreta were seen. On the  32nd week, the  planned caesarean hysterectomy was performed. The balloon catheters to occlude the internal iliac arteries and minimize bleeding during the surgery were used. Conclusions. Antenatal diagnosis of placenta percreta is especially important. Methods of visual diagnostics are complementary. The optimal surgical approach during caesarean hysterectomy remains controversial. In the case of the slow oozing without a clearly identified source of bleeding after hysterectomy and internal iliac arteries balloons deflation, ligation of one of the internal iliac arteriescan be reasonable to avoid residual haemorrhage and relaparotomy.
Keywords: antenatal diagnostics; visual diagnostics; placenta percreta; placenta previa